SCOPE OF MEDICAL COLLEGES IN PRIVATE SECTOR - KHAN, A.J. SI (Journal of Ayub Medical College Abbottabad, 2004)
Medical profession is still the most sought after profession, there are thousands of bright students who pass their F.Sc examination in First Division and desire to join medical colleges but are unable to get admission in government medical colleges. There is a great shortage of doctors in the country. Hundreds of young students go abroad for medical education, costing huge sum of foreign exchange to the families and to the government spending 5 to 7 years and obtaining degrees which are not recognized in Pakistan. Therefore to fulfill the demand of the public, and to overcome the shortage of doctors in the country and to save the valuable foreign exchange, private sector medical colleges are much needed in Pakistan. However, establishment of medical colleges is very expensive and difficult. PMDC is very firm in implementing its rules and regulations. Those colleges which fulfill the laid down requirement of PMDC, help in overcoming the shortage of doctors in the country and provide much needed health care to the population. Such medical colleges are much appreciated by the public and by the govt. Such private sector medical colleges have great future and some of them may become famous and outstanding like the private sector medical colleges in the USA.